Auditoria al proceso de compra de inventarios de la empresa Orocash de la ciudad de Babahoyo en el año 2022. - Narváez Espín, Telmo Mauricio (2022)
The present case of trying to analyze the purchasing process of the organization Orocash S.A. through the execution of a study of an internal control audit of the current period, to verify and offer compliance with the operational activities to be developed within said institution, for the analysis a sequence of consequent purposes was proposed through an exploratory design– descriptive under a qualitative paradigm, where a general study of the purchasing process was made in the C.O.SO. Bearing in mind the 5 elements that make up said report, where the value of internal control in the purchasing process was identified, which action strategies are proposed, tools were used for the due ones, having as a guide to document review and check lists for the review and evaluation of the dangers in the internal control that will allow strategic occupations in the short, medium and long term for the purchasing process.